Integration of Building Information Modelling (BIM) in Design Process to Enhance Building Energy Performance - Kong, Sio Kah; Aw, Mun Yi; Lee, Benny, Hai Chim (INTI International University, 2020)
The increment in building energy consumption has become a global issue that needs to be attended and curbed in order to move towards the goal of sustainability. One of the essential measures to enhance the building energy performance is by carrying out building energy analysis to understand the energy demand of a building. Unfortunately, energy analysis is very seldom performed in traditional design process and this causes the building energy consumption cannot be predicted during early design stage. Consequently, the buildings require large amount of energy to operate. BIM, an advancement of technology with various features, is believed to have the potential to overcome this trouble. The aim of this study is to examine the integration BIM in design process in relation to the enhancement of building energy performance in Malaysia. To properly tackle the problem of high building energy usage, the factors of affecting building energy consumption are identified. Then, the numerous benefits that BIM can offer to enhance the building energy performance are also determined in this study. Since this study is more relevant to design consultants, online questionnaire is distributed to architect and engineers in Selangor area to obtain their perspectives regarding this topic. The primary data collected is presented in pie chart as well as bar chart and then is analysed by statistical tools like Relative Importance Index (RII) and mean one sample t-test. The research findings show that the physical characteristic of buildings is determined as the main factor that influences the building energy consumption. Meanwhile, it is justified that the benefits of applying BIM in design process are significant in enhancing building energy performance. The most significant benefit is reducing the absorption of heat energy from the surrounding.